Eficacia del trampeo en el control de broca del café (Hypothenemus hampei), con dos variedades arábigas establecidas en tres densidades de siembra y en dos localidades del cantón Caluma. - Camacho Fierro, Anderson Becker (2019)
The present research work was carried out in the towns of the Experimental Farm El Trunfio and Pita, located in the Bolívar province, Caluña canton. The objectives of this research were: validate the use of trapping as a technology for the control of the bit of coffee in the area of Caluma; and evaluate the efficacy of traps with alcohols in three densities and two varieties of Arabica coffee in two localities of Caluma. The experimental design used was incomplete block random, where the treatments evaluated the influence of the factors varieties, population densities and locations, where traps-based alcohols was used to verify the capture of bit of the coffee bean. According to the results, manifests that the initial incidence levels of bit of coffee were 3.3 to 3.6% for Catucaí; the density factor increased incidence levels were for the treatment of 6000 pl / has with 3.8 to 4.1%. Also indicated that the town of La Pita recorded higher levels of incidence between 3.5 to 4.1% compared to El Triunfo. With the use of traps based on spirits, the largest number of bits captured on average was 23 bits in the triumph and 12 bits in La Pita, both in Catucaí; This allowed for lower levels to values of 1.6 per cent lower incidence in both study sites